Arthroscopic Subtalar Arthrodesis after a Calcaneus Fracture Covered with a Forearm Flap. (29th December 2010) - Michels, Frederick; Stockmans, Filip; Guillo, Stéphane; Van Der Bauwhede, Jan; Oosterlinck, Dirk
Abstract : Surgical treatment of intraarticular calcaneal fractures is often associated with postoperative wound problems. Soft tissue necrosis, bone loss and uncontrollable infection are a challenge for the surgeon and amputation may in some cases be the ultimate solution. A free flap can be very helpful to cover a significant soft tissue defect and help in fighting the infection. However, the free flap complicates the surgical approach if subtalar arthrodesis and bone reconstruction are needed. This study demonstrates the value of an arthroscopic technique to resect the remaining articular cartilage in preparation for subtalar arthrodesis and bone grafting. This approach avoids compromising the soft tissues and minimizes damage to the free flap.